Discrete element models for understanding the biomechanics of fossorial animals. Issue 9 (16th September 2022) - Gong, Hao; Adajar, Joash B.; Tessier, Léa; Li, Shuai; Guzman, Leno; Chen, Ying; Qi, Long
Abstract: The morphological features of fossorial animals have continuously evolved in response to the demands of survival. However, existing methods for animal burrowing mechanics are not capable of addressing the large deformation of substrate. The discrete element method (DEM) is able to overcome this limitation. In this study, we used DEM to develop a general model to simulate the motion of an animal body part and its interaction with the substrate. The DEM also allowed us to easily change the forms of animal body parts to examine how those different forms affected the biomechanical functions. These capabilities of the DEM were presented through a case study of modeling the burrowing process of North American Badger. In the case study, the dynamics (forces, work, and soil displacements) of burrowing were predicted for different forms of badger claw and manus, using the model. Results showed that when extra digits are added to a manus, the work required for a badger to dig increases considerably, while the mass of soil dug only increases gradually. According to the proposed efficiency index (ratio of the amount of soil dug to the work required), the modern manus with 5 digits has indeed biomechanical advantage for their fossorial lifestyle, and the current claw curvature (25.3 mm in radius) is indeed optimal. The DEM is able to predict biomechanical relationships between functions and forms for any fossorial animals. Results can provide biomechanical evidences for explaining how the selective pressures for functions influence the morphological evolution in fossorial animals. Abstract : The dynamics (forces, work, and soil displacements) of burrowing by North American Badger were predicted for different forms of badger claw and manus, using numerical models. The results indicate that the modern manus with 5 digits has indeed advantages. The findings provide biomechanical support for the evolutionary optimization of badgers' manus for their fossorial lifestyle.